Marketing the Image of the Modern Muslim Woman in the Age of Black Lives Matter - Wheeler, Kayla Renée (Journal of religion, media and digital culture, 2022)
Using a feminist critical discourse analysis, this article examines modest dress stylist Hakeemah Cummings’ Instagram posts from December 2019 to July 2021 to show how she constructs the image of the “modern Muslim woman.” Cummings represents a postfeminist woman who believes it is possible to have it all—a successful career and a happy family, all while looking beautiful and being modest. As an influencer, she markets this image of the “modern Muslim woman” to her followers on Instagram, showing them that they too can have a similar life if they consume particular products and perform certain actions. I argue that Cummings has expanded the definition of the “modern Muslim woman” to include a commitment to racial justice, following the Prophetic model of supporting marginalized community. Rather than dismantling the “modern Muslim woman” image, which traditionally excludes Black women, she expands the image to center Black women and Black issues.